Pengaruh Media Pop-Up Book Terhadap Pemahaman Konsep IPAS Pada Siswa Kelas IV Kota Bengkulu - Sukma, Apriana; Yusnia (JURIDIKDAS, 2025)
This research aims to determine the influence of pop-up book on the ability to understand the IPAS concept of landscape material in Bengkulu in grade IV students in Bengkulu City. This research is quantitative research using the quasy experiment method and the Matching Only Pretest-Posttest Control Group Design type of research design. The population in this study was class IV in Bengkulu City. The instrument used is a written test sheet in the form of multiple choice questions totaling 10 questions with data collection techniques in the form of pretest and posttest questions. The data analysis techniques used are descriptive statistical tests, prerequisite tests (normality and homogeneity tests), and inferential/hypothesis tests. The results of the hypothesis test obtained from the average posttest value and tested using the independent sample t-test show that the thitung value using Equal Variences Assumed = 2,910 and the Sig value. (2-tailed) has a value of 0,005 and the ttable distribution value is 2,000, so that the thitung > ttable (2,910 > 2,000) and Sig. (2-tailed) 0,005 < 0,05. This shows that there is a different understanding of the IPAS concept in the experimental and control groups caused by the treatment of the two different groups. Based on this test, H0 was rejected and Ha was accepted, so it can be concluded that there is an influence of the pop-up book media on the ability to understand the IPAS concept of landscape material in Bengkulu among class IV students in Bengkulu City.